Identification of autophagy-related key biomarkers in caerulein induced acute pancreatitis: In silico and in vivo study - Xinzhuang Shen; Jie Yao; Zongke Wang; Renhua Chen; Laian Li; Xiangjun Xu; Yongming Huang (PLoS ONE, 2026)
Background Dysregulated autophagy is known to play a crucial role in the pathogenesis of Acute pancreatitis (AP). However, its specific mechanisms remain unclear. The present study aimed to elucidate the mechanism of autophagy-related genes (ARGs) by bioinformatics analysis and experimental validation in AP. Methods GSE109227, GSE65146, and GSE3644 were obtained from GEO database and underwent standardization and principal component analysis. ARGs were sourced from the Human Autophagy Database. Differentially expressed genes (DEGs) were intersected with ARGs to identify differentially expressed autophagy-related genes (DEARGs) associated with AP. Subsequently, functional enrichment analysis, Gene Set Enrichment Analysis, and Gene-gene interaction networks were performed. The expression of DEARGs at the mRNA level was verified using the GSE121038 dataset, and protein expression levels were examined in animal model by western blot. Potential regulatory chemicals or compounds affecting the expression of DEARGs were predicted using the Comparative Toxicogenomics Database (CTD). Results We screened seven key biomarkers (Sesn2, Kras, Hmox1, Cast, Nfe2l2, Npc1, and Cdkn1a) from the GSE109227, GSE65146, and GSE3644 datasets. These biomarkers showed higher levels of mRNA expression compared to the control group. Additional testing using the GSE121038 dataset showed that only Npc1 mRNA level was not significantly different (P > 0.05). The protein expression levels of Sesn2, Hmox1, and Kras aligned with mRNA expression, while Nfe2l2, Cast, and Npc1 showed opposing patterns. No differences were detected in Cdkn1a. GSEA revealed significant enrichment of the ARG set in AP samples across the three GEO datasets. Functional enrichment analysis indicated the DEARGs primarily participate in the regulation of autophagy and macroautophagy. Several chemicals or compounds were projected to modulate DEARGs expression, notably acetaminophen. Conclusion Our research further highlights the significant interaction between autophagy and AP. Notably, Sesn2, Kras, Hmox1, and Nfe2l2 exhibited significant expression differences during acute pancreatitis, suggesting they may serve as potential biomarkers for the condition.